EFEKTIVITAS KERJA WORK FROM HOME (WFH) TENAGA AHLI DPR RI DI MASA PANDEMIK COVID-19 - Zahera Mega Utama (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This study aims to determine the effect of work planning and supervision on the effectiveness of work from home (WFH) experts in the DPR RI. The hypotheses tested are (1) There is a significant influence between Work Planning and Effectiveness; (2) There is a significant influence between Supervision and Effectiveness; and (3) There is a significant influence between Work Planning and Effectiveness together with Effectiveness. This research was conducted using a survey method with an associative descriptive approach. The sample was taken using the simple random sampling technique, while the research data collection instrument for the variable work planning and effectiveness and effectiveness was using a questionnaire. The results of the study concluded that first there is a positive and significant relationship between Work Planning and Effectiveness with a Pearson Product Moment correlation number of 0.867 or 75.1% X1 affects Y which is shown in the regression equation Ŷ = 2.351 + 1.022X1. Second, there is a positive and significant relationship between Supervision and Effectiveness with the Pearson Product Moment correlation number of 0.719 or 51.7% X2 has an effect on Y, which is shown in the regression equation Ŷ = 3,100 + 0.866 X2. Third, there is a positive and significant relationship between Work Planning and Supervision together with Effectiveness with a Pearson Product Moment correlation number of 0.874, which is shown in the regression equation Ŷ = 3,732+ 0.874 X1 + 0.205 X2, the Coefficient of Determination 0.764 indicates that Work Planning and Supervision contributed 76.4% to the Work From Home (WFH) Effectiveness of the DPR RI Experts.